(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Medical education in Bangladesh is totally controlled by the Government and run a unique undergraduate curriculum throughout the country in both public and private sectors. This paper is aimed to briefly describe the medical education reform in Bangladesh and suggests further assessment changes. The present official form of undergraduate medical curriculum has first evolved in 1988 followed by revision in 2002 and 2012. Assessment and teaching are the two sides of the same coin. Assessment drives learning and learning drives practices. Following the curriculum reform since 2002, the assessment in undergraduate medical education has been greatly changed. There are a lot of in-course formative assessments which include item examination, card final and term final, designed to improve the quality of education. Ten percent marks of summative written examinations derive from formative assessment. Traditional oral examination has been changed to structured form to ensure greater reliability. Even then, teachers are not yet building up to conduct oral examination in such a structured way. Examiners differ in their personality, style and level of experience with variation of questioning and scoring from student to students. Weakness of reliability on oral examination still exists. Students also feel very stressful during the oral examinations. Moreover, to conduct such oral examination, three to four months times per year are lost by the faculties which can be efficiently utilised for teaching and research purposes. Worlds’ leading medical schools now-a-days used oral examination only for borderline and distinction students. Bangladesh also must consider oral examination only for borderline and distinction students. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16658 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 357-363